Wellness in cognitive workload - a conceptual framework - Pereira, Eduarda Manuel Barros (2019)
Driving is a highly complex task, comprising over 1600 separate tasks over five behavioural levels. 94% of road accidents occur by human faults. Drivers simultaneously control the vehicle, adjust speed and trajectory, deal with hazards, evaluate progress towards their goal, and make strategic decisions such as navigation. Novel technologies such as active cruise control and active steering are intended as comfort systems for the driver because they are designed to relieve the driver of workload. One could go further and imagine whether cars could be created so as to get to know their user and use that knowledge to recognise the user and be more safe. A cooperative driving leads to automotive systems with impacts on mental workload. Of particular concern in this study are the twofold areas. On the one hand the personalization of the car to the user and on the other, its customization. Using the principles of cognitive ergonomics, the main purpose is to allow more features to people, whilst providing comfort and trust in the human machine interface which (1) diagnoses the driver’s state and uses additional monitoring devices (2) to provide feedback about driver´s behaviour as well as awareness and wellness.